The “wild shot”: photography for more biology in natural history collections, not for replacing vouchers - Garrouste, Romain (Zootaxa, 2017)
Recently a correspondence in Zootaxa (Ceríaco et al., 2016) with more than 450 signatories including taxonomists, curators and other taxonomy users from all continents has received wide attention and has stimulated extensive discussion (a true buzz) around the possible interpretations of the Code (ICZN) about photography in taxonomy (Researchgate website link). This short note was necessary to recall the necessity of preserved specimens as vouchers for taxonomy, in response to photography-based taxonomy (PBT) as defended by Pape et al. (2016), and in a broad sense, for all the life sciences. This had been widely discussed and argued by Dubois & Nemésio (2007) who concluded on the importance of vouchers in taxonomy. But if the subject of these papers and discussions are about photography as the only way to document a new species, none of them discussed really what photography could represent in enhancing knowledge in natural sciences based on collections of specimens including type series and in association with other media (video and sound).